2015
DOI: 10.1371/journal.pone.0138650
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Sequencing for Evaluation of Genetic Stability of Influenza A/California/07/2009 (H1N1) Vaccine Viruses

Abstract: Virus growth during influenza vaccine manufacture can lead to mutations that alter antigenic properties of the virus, and thus may affect protective potency of the vaccine. Different reassortants of pandemic "swine" H1N1 influenza A vaccine (121XP, X-179A and X-181) viruses as well as wild type A/California/07/2009(H1N1) and A/PR/8/34 strains were propagated in embryonated eggs and used for DNA/RNA Illumina HiSeq and MiSeq sequencing. The RNA sequences of these viruses published in NCBI were used as references… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…To establish animal models of H1N1 aerosol inhalation by simulating the natural infection, we chose to expose BALB/C mice to influenza A/California/07/2009, which has caused global pandemic outbreaks since 2009 and is responsible for the increased H1N1‐associated morbidity and mortality in China to date. Influenza A/California/7/2009 is still the prototype H1N1 strain recommended by the WHO for the current seasonal vaccine, and recent studies have revealed that other clades of H1N1 viruses are antigenically similar to the A/California/7/2009 strain …”
Section: Discussionmentioning
confidence: 99%
“…To establish animal models of H1N1 aerosol inhalation by simulating the natural infection, we chose to expose BALB/C mice to influenza A/California/07/2009, which has caused global pandemic outbreaks since 2009 and is responsible for the increased H1N1‐associated morbidity and mortality in China to date. Influenza A/California/7/2009 is still the prototype H1N1 strain recommended by the WHO for the current seasonal vaccine, and recent studies have revealed that other clades of H1N1 viruses are antigenically similar to the A/California/7/2009 strain …”
Section: Discussionmentioning
confidence: 99%
“…All sequences were aligned, using MAFFT v7.388, against the A/California/07/2009 reference strain circulating among people at that time ( 9 12 ). We observed a high degree of similarity (>99%) among all six strains as well as the reference strain (similarity levels are presented in Table 1 ).…”
Section: Announcementmentioning
confidence: 99%
“…Trimmed sequence reads of each sample were analyzed by using Kraken (Wood & Salzberg, 2014) and CLARK (31-mers) (Ounit et al, 2015) in order to identify and estimate the proportion of mapped reads of known bacterial, viral, and human genome sequences. Trimmed sequence reads of each sample were taxonomically classified by using high accuracy Kraken tool (Majid et al, 2015;Wood & Salzberg, 2014). However, since Kraken does not provide a human database, CLARK (Ounit et al, 2015) was used to identify and estimate the proportion of mapped reads of known bacterial, viral, and human genome sequences.…”
Section: Ngs Data Analysismentioning
confidence: 99%